A Soldier's Story of His Regiment (61st Georgia) : And Incidentally of the Lawton-Gordon-Evans Brigade Army of Northern Virginia - Nichols, G. W. (George Washington), 1843-1916 (Book collections on Project MUSE., 2011)
George W. Nichols aptly titled Soldier Story is one of the classic narratives of frontline infantry service in the Army of Northern Virginia. Nichols 61st Georgia fought in the renowned brigade commanded in turn by General Alexander r. Lawton, General John B. Gordon, and General Clement A. Evans. Nichols framed his account without sentimental hindsight; in addition to reporting great battles and dramatic moments, he told the story of two cousins killing each other in a quarrel about cooking duties and described maggot-infested corpses around Spotsylvania.